Sarcoidosis and COVID-19 - V. L. Dobin; I. V. Panin (Туберкулез и болезни лёгких)
The review analyzes 21 publications on sarcoidosis pathogenesis, clinical course, treatment characteristics (sarcoidosis in the COVID-19 era), and prognostic aspects during the COVID-19 pandemic.